Evolution led humans to bipedalism, but we live in a sedentary society: Will “Sunday running” protect us from NCDs at no cost? - Presta, Valentina; Gobbi, Giuliana; Condello, Giancarlo; Carubbi, Cecilia; Masselli, Elena; Mirandola, Prisco; Vitale, Marco (Frontiers in Public Health, 2023)
Evolution led humans to bipedal stance and moving. However, we live in a sedentary society that strongly challenges our willingness to be physically active. We (mis)understand that being at least a Sunday runner could protect us from sedentary-related diseases, but what if this compromises the healthier life expectancy anyway? Citing Paul Gauguin, we know where we do come from and what we are, question arises about where we are going. And also, how.